Fungi of vegetable crops in Rio Grande do Sul - Luz, Ney Kremer (Pesquisa Agropecuaria Brasileira, 2014)
This paper lists the names of pathogenic fungi which were observed, during the past 30 years, on 38 vegetable crops. The study was conducted by the Secretary of Agriculture of the state of Rio Grande do Sul, Brazil. A total of 74 valid binomials are listed in addition to 28 generic names without species determination. Included in the study is a review of the available data giving remarks about some species, observed synonymy, references to the materials represented in the herbarium, common names of diseases and references to literature.